Evaluation of PIAT UGM Herbal Drink: SWOT Analysis - Hani Perwitasari; Fatkhiyah Rohmah; Triya Andriyani; Anggun Pramudita (Agriekonomika, 2023)
Herbal drinks provide very promising business potential as people become more aware of the benefits of living a back-to-nature lifestyle. This trend is also an opportunity for processed herbal drink products made by PIAT UGM, such as Rosegar, Gilegrass, and Segar Ayu. The purpose of this study is to evaluate the development of these three products using descriptive analysis based on primary data. The data was gathered from five PIAT UGM employees and ten customers and analyzed with a SWOT analysis. The results of this study revealed that the priority development strategy that can be applied is the Strengths-Threats strategy, through strengthening the branding of high-quality products, tested flavors, and BPOM-registered. In addition, PIAT needs to optimize product promotions through social media and scheduled basis to penetrate various groups, make products as official merchandise for UGM, and collaborate with gift shops and travel agents in the Special Region of Yogyakarta.